Understanding Policy Domains their Salient Forces and Organisational Challenges - Chirawu, Tapera O. (Book collections on Project MUSE., 2012)
Understanding Policy Domains: Their Salient Forces and Organisational Challenges examines the complexity of policy making processes within the context of human action arising from culture, life necessities and politics. It provides an understanding of human, environmental and institutional behaviour, and identifies the policy factors that underline the success or failure of governments and institutions. This book provides policy-makers, practitioners and other researchers in the field with a clear understanding of the process of policy-making and who is responsible for what. It sets the tone for academics and policy practitioners to confront the problems and challenges that countries face as they seek to improve governance and service delivery. The author provokes debate on the cause and effect of past, present and future human actions, bringing into play the issues of honesty, transparency and political will. He promotes policy as a way towards achieving social harmony in the human struggle for survival. User-friendly for both students and lecturers, as well as for researchers, government and NGO policy "gurus", Understanding Policy Domains, their Salient Forces, and Organisational Challenges is also valuable for political parties whose members are often unaware of this important aspect of government responsibility